Perancangan Parameter Proses Produksi Untuk Peningkatan Kualitas Produk Pipa Baja Dengan Metode Taguchi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Taguchi Method is one of quality by design tools which discovers optimum design parameters by statistical approached. Of these, the method gains effectiveness and efficiency from its philosophy background of "loss function". This research implemented Taguchi Method into pipe-manufacturing industry. The manufactured products in this industry required high precision level in order to provide outstanding service level on demand. Therefore, minimum "inner-outer weld bead" is the objective of this research. The results showed that objective could be achieved by proposing new parameters